PERANCANGAN SITEM PENGUKURAN KINERJA DENGAN METODE HR SCORECARD PADA SUB-BIDANG SDM PT PLN (PERSERO) PUSAT PENGATUR BEBAN (P2B) KANTOR INDUK - Mustika Ayu Permata S.; Eric Wibisono; Benny Lianto (CALYPTRA, 2018)
P2B as a key unit to the success of operational business processes in PLN needs to conduct performance measurement to determine whether the performance of the organization and its employees are in accordance with the requested targets. Therefore, the researcher offers a method of me asuring HR Scorecard which is a form of human resources measurement to demonstrate the role of human resources that has been regarded as intangible to be measured in their role to a chieve the company’s mission, vision and strategy. The design of HR Scorecard resulted 17 indicators on four existing perspectives. Then the achievement target and its performance of each indicator we re measured and assessed. The pairwise comparison method (A HP) was done to w eigh each p erspective, strategy and indicator obtaining nine greatest weights of indicators. The indicator is then displayed in the dashboard to show the data of perf ormance measurement results. Thus the results show that the strategic perspective and consumers were good with each performance value of 4.197 and 3.667. Meanwhile, the operating and financial performance perspectives were quite well with the performance value of 2.968 and 2.667. It can be calculated that the value of the overall performance is 3.538 which means good performance.